2011
DOI: 10.1111/j.1095-8312.2011.01777.x
|View full text |Cite
|
Sign up to set email alerts
|

Shape and sound reveal genetic cohesion not speciation in the New Zealand orthopteran, Hemiandrus pallitarsis, despite high mitochondrial DNA divergence

Abstract: Levels of neutral mitochondrial (mt)DNA sequence diversity play a prominent role in alpha taxonomy, with divergence thresholds of approximately 3% widely being accepted as indicative of species differences. However, a number of studies of New Zealand invertebrates conclude that intraspecific mtDNA divergences are commonly much higher. We investigated the diversity and distribution of mitochondrial cytochrome oxidase I DNA sequences from populations of the New Zealand ground weta Hemiandrus pallitarsis with res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 80 publications
0
24
0
Order By: Relevance
“…Male H. pallitarsis were the larger of the two taxa according to metafemur length (t = −2.48, P < 0.05). The sample size was too small to test sexual size dimorphism for H. maculifrons, but adult males are generally smaller than adult females in both species (Chappell et al 2012(Chappell et al , 2014. However, as a result of the difficulty of accurate identification in the field, the smaller H. maculifrons individuals measured may be late instars rather than adults.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Male H. pallitarsis were the larger of the two taxa according to metafemur length (t = −2.48, P < 0.05). The sample size was too small to test sexual size dimorphism for H. maculifrons, but adult males are generally smaller than adult females in both species (Chappell et al 2012(Chappell et al , 2014. However, as a result of the difficulty of accurate identification in the field, the smaller H. maculifrons individuals measured may be late instars rather than adults.…”
Section: Resultsmentioning
confidence: 98%
“…The two species of interest in this study are both common and widespread: Hemiandrus pallitarsis (Walker, 1869) which occurs across most of the North Island, and Hemiandrus maculifrons (Walker, 1869) which is found in both the North and South Islands (Pratt et al 2008;Chappell et al 2012; although it is probably a species complex; B Taylor Smith, pers. comm.…”
Section: Introductionmentioning
confidence: 99%
“…Our phylogenetic relationships within the opsariichthine group were mostly concordant with previous studies (Huang, Wang, & Wang, ), and three main groups were found: the Candidia ‐ Parazacco ‐ Nipponocypris group with one longitudinal stripe on the flanks, the Zacco group with an indistinct vertical stripe or band on the side of the body, and the Opsariichthys group with several distinct vertical stripes or bands along its body. Earlier studies proposed that the levels of mitochondrial DNA sequence diversity play a prominent role in taxonomy, with divergence thresholds of approximately 3% widely being accepted as indicative of species differences (Chappell et al, ; Hebert et al, ; Johnston et al, ). The present results showed that, when a 3% genetic distance was used as a threshold for species delimitation, there were 35 haplogroups in the opsariichthine mitochondrial phylogeny, nine haplogroups in Candidia ‐ Parazacco ‐ Nipponocypris group, six haplogroups in the Zacco group, and 20 haplogroups in the Opsariichthys group, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…obs.). Some ecological research has been undertaken on Hemiandrus maculifrons (Walker, 1869) (Cary 1983), Hemiandrus subantarcticus (Salmon, 1950) (Butts 1983), Hemiandrus 'peninsularis'/'horomaka' (Wahid 1978) and Hemiandrus pallitarsis (Walker, 1869) (Gwynne 2002(Gwynne , 2004(Gwynne , 2005Chappell et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Reduction in ovipositor length has therefore been inferred as having occurred at least three times in the New Zealand Hemiandrus (Pratt et al 2008). Of the seven putative species with extremely short ovipositors (Johns 2001), six are narrow endemics (Chappell et al 2012). Two species, Hemiandrus maia sp.…”
Section: Introductionmentioning
confidence: 99%